Fabrication and characterization of nickel silicide nanowire electrodes by solid-state diffusion controlled growth for supercapacitor / Mohammad Mukhlis Ramly - Mohammad Mukhlis , Ramly (2021)
The growth of nickel silicide nanowires (Ni3Si2 NWs) using solid-phase diffusion controlled growth were studied in this work. The Ni3Si2 NWs were grown on Ni foil and Ni foam substrates coated with Ni film using a home-built chemical vapor deposition (CVD) system. The studies started with the effect of silane (SiH4) flow-rate and substrate temperature on the growth, structure, and electrochemical properties of the NWs. Ni3Si2 NWs were grown on Ni foil by optimizing SiH4 flow-rate (1 to 5 sccm) and substrate temperature (350 to 500°C). These variations produced a different type of Ni3Si2 NWs morphologies such as dendritic, ultra-thin, and root-tips. The ultra-thin NWs have an average diameter and length of 16 ± 3 nm and 6.5 ± 0.5 ?m respectively, with the aspect ratio of 406. Next, the optimization of the growth parameters to obtain high quality of Ni3Si2 NWs was carried out by varying Ni film thickness in between 90 ± 5 and 220 ± 5 nm. These NWs exhibited morphology of straight NWs with diameter and length between 16 to 23 nm and 2.9 to 3.9 ?m, respectively. Based on these three optimized parameters, the high-density Ni3Si2 NWs demonstrated the highest specific capacity value with a maximum value of 330.5 C/g at current density 1 A/g. In the last part of this thesis work, the optimum parameters from the three variations were selected to growth Ni3Si2 NW with high density and straight nanowire morphology, and high electrochemical performances, to fabricate a hybrid supercapacitor electrode. The supercapacitor performance of Ni3Si2 NW-based electrode on Ni foil and foam was evaluated and compared. This highly dense packed thin, straight, and long morphologies NWs on Ni foam have an average length and diameter of 12.5 ± 0.3 ?m and 13 ± 2 nm respectively, with a high aspect ratio of 961 owing to their extremely large surface area (5.184 x 1011 NWs/cm2). The fabricated Ni3Si2 NWs/activated carbon-based asymmetric supercapacitor exhibited a maximum specific capacity of 578.3 C/g, an energy and power density of 62.24 Wh/kg at 387.5 W/kg respectively, together with a good cyclic stability with 76 % capacity retention after 3000 cycles. The correlations of the electrochemical performances with their morphology, compositions, and structural properties of Ni3Si2 NWs are summarized at the end of the thesis.